How Accurate Is Coarse-grained Clone Detection?: Comparision with Fine-grained Detectors - Hotta, Keisuke; Yang, Jiachen; Higo, Yoshiki; Kusumoto, Shinji (Electronic Communications of the EASST, 2014)
Research on clone detection has been quite successful over the past two decades, which produced a number of state-of-the-art clone detectors.However, it has been still challenging to detect clones, even with such successful detectors, across multiple projects or on thousands of revisions of code in limited time.A simple and coarse-grained detector will be an alternative of detectors using fine-grained analysis.It will drastically reduce time required for detection although it may miss some of clones that fine-grained detectors can detect.Hence, it should be adequate for a tentative analysis of clones if it has an acceptable accuracy.However, it is not clear how accurate such a coarse-grained approach is.This paper evaluates the accuracy of a coarse-grained clone detector compared with some fine-grained clone detectors.Our experiment provides an empirical evidence about acceptable accuracy of such a coarse-grained approach.Thus, we conclude that coarse-grained detection is adequate to make a summary of clone analysis and to be a starter of detailed analysis including manual inspections and bug detection.